Aspects of Justice in Business Contracts Force Majeure Study on Franchise Agreements in the Covid-19 Period - Bonaraja Purba; Dyamawani Purba; Enwanda Sinaga; Hwan Daniel (PT FORMOSA CENDEKIA GLOBAL, 2023)
The agreement, in essence, is an agreement, characterized by meeting the will (meeting of mind, mutual assent) of the parties to achieve an agreed goal in order to provide the maximum possible benefit for the parties. As a conclusion, justice has not been achieved for the parties, especially the franchisee, due to the very strong bargaining position of the franchisor, which is not balanced when comcpared to the weak bargaining position of the franchisee. This has an impact on the contents of the contract which is fully made by the franchisor, which of course tends to provide the greatest benefit to the franchisor. Force majeure or force majeure can be in the form of earthquakes, fires, floods, landslides, wars, military coups, embargoes, epidemics, and so on. During the corona pandemic, which is currently hitting all parts of the world, of course it has an impact on the implementation of a business contract. This paper examines force majeure in an agreement that occurred during the corona virus pandemic which cannot automatically be used as a reason for canceling a business contract, but can be used as a way to negotiate in canceling or changing the contents of the contract.